2015
DOI: 10.1177/0363546515599628
|View full text |Cite
|
Sign up to set email alerts
|

Hip Strength Is Greater in Athletes Who Subsequently Develop Patellofemoral Pain

Abstract: Background Hip and knee strength abnormalities have been implicated in patellofemoral pain (PFP) in multiple studies. However, the relationship is unclear, as many of these studies have been retrospective. Purpose To compare prospective hip and knee isokinetic strength in young female athletes who subsequently went on to develop PFP relative to their uninjured, healthy peers. Study Design Descriptive epidemiology study. Methods Adolescent female athletes (N = 329) were tested for isokinetic strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 53 publications
0
42
1
1
Order By: Relevance
“…Quadriceps weakness was not identified as a risk factor for future PFP in an adolescent group 27. While this further validates the importance of investigating risk factors within homogenous groups, it is also important to consider the implications of these findings in relation to risk modification interventions within differing populations.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Quadriceps weakness was not identified as a risk factor for future PFP in an adolescent group 27. While this further validates the importance of investigating risk factors within homogenous groups, it is also important to consider the implications of these findings in relation to risk modification interventions within differing populations.…”
Section: Discussionmentioning
confidence: 60%
“…When the data were pooled for the adolescent cohort, there is moderate evidence from one HQ27 and one MQ study26 that increased hip abduction strength is a risk factor for future PFP ( I 2 =0%, SMD 0.71, CI 0.39, 1.04) (see figure 12B) when measured isometrically with a HHD. Data pooling was not possible for the military or recreational runner subgroups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other studies, 2, 10 also focused on adolescent cohorts with patellar instability, reported higher rates of dislocation in adolescent patients with increased distance between the tibial tuberosity and trochlear groove (TT-TG). Finally, studies 19, 26, 27 have identified increased hip and knee abduction moments as risk factors for the development of PFP in adolescents. While the implied consequence of these abnormalities is altered patellofemoral tracking patterns and increased patellofemoral contact pressures, confirmation of these fundamental findings in adolescent females with PFP is currently lacking.…”
Section: Introductionmentioning
confidence: 98%